1994
DOI: 10.1007/bf02017671
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral osteomyelitis due to intraosseous infusion: Case report and review of the English-language literature

Abstract: Intraosseous infusion, a mode of peripheral access largely abandoned in the 1940s and 1950s, is becoming increasingly popular in the setting of pediatric crisis. While complications are rare when the procedure is properly performed, the risk of osteomyelitis increases with prolonged infusions. We present a case of bilateral osteomyelitis secondary to intraosseous infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…It is possible that plastic/ reconstructive surgery consultation would have been necessary had this child survived. Despite case reports of osteomyelitis following IO infusions (20), a meta-analysis review of 4,270 cases of IO use found 27 (0.63%) cases of osteomyelitis (21). With a maximal placement time of 36 hrs, we did not identify any cases.…”
Section: Discussionmentioning
confidence: 82%
“…It is possible that plastic/ reconstructive surgery consultation would have been necessary had this child survived. Despite case reports of osteomyelitis following IO infusions (20), a meta-analysis review of 4,270 cases of IO use found 27 (0.63%) cases of osteomyelitis (21). With a maximal placement time of 36 hrs, we did not identify any cases.…”
Section: Discussionmentioning
confidence: 82%
“…Infection can take the form of cellulitis or in more severe cases osteomyelitis [3]. When the tibia is used as an IO access site extravasation of fluid can lead to compartment syndrome which may go undetected in the obtunded patient [4].…”
Section: Discussionmentioning
confidence: 99%
“…Some children presenting with acute virulent onset of disease, including high fever, rapid onset of symptoms and severe borte pain, may have "cold" bone lesions with decreased uptake in borte on the initial imaging study delayed views [164][165][166][167][168][169]. Delayed "cold" borte scans usually however, show evidence of increased hyperemia in the blood flow and blood pool phase of the study at the margins of the inflammatory process.…”
Section: Musculoskeletal Infection and Inflammationmentioning
confidence: 99%